Recent advances in polymeric microparticle-based drug delivery systems for knee osteoarthritis treatment - Wang, Guangxin; Zhang, Xin-an; Kapilevich, Leonid; Hu, Mingjie (Frontiers in Bioengineering and Biotechnology, 2023)
Due to the poor bioavailability and high joint clearance of drugs, sustained delivery of therapeutic agents has proven difficult in the treatment of osteoarthritis (OA). Intra-articular (IA) drug delivery strategy is an attractive option for enhancing OA patients’ prognosis, for which various polymer materials have been used as drug carriers due to their attractive delivery properties, to slow or even reverse the progress of OA by prolonging the duration of therapeutic agent residence in the joint. This article focuses on the recent developments in natural and synthetic polymer-based microsphere drug delivery systems for treating knee osteoarthritis. It evaluates the translational potential of some novel formulations for clinical application.